GTP Cyclohydrolase I and Tyrosine Hydroxylase Gene Mutations in Familial and Sporadic Dopa-Responsive Dystonia Patients - Cai, Chunyou (Public Library of Science, 2013)
Dopa-responsive dystonia (DRD) is a rare inherited dystonia that responds very well to levodopa treatment. Genetic mutations of GTP cyclohydrolase I (GCH1) or tyrosine hydroxylase (TH) are disease-causing mutations in DRD. To evaluate the genotype-phenotype correlations and diagnostic values of GCH1 and TH mutation screening in DRD patients, we carried out a combined study of familial and sporadic cases in Chinese Han subjects. We collected 23 subjects, 8 patients with DRD, 5 unaffected family members, and 10 sporadic cases. We used PCR to sequence all exons and splicing sites of the GCH1 and TH genes. Three novel heterozygous GCH1 mutations (Tyr75Cys, Ala98Val, and Ile135Thr) were identified in three DRD pedigrees. We failed to identify any GCH1 or TH mutation in two affected sisters. Three symptom-free male GCH1 mutation carriers were found in two DRD pedigrees. For those DRD siblings that shared the same GCH1 mutation, symptoms and age of onset varied. In 10 sporadic cases, only two heterozygous TH mutations (Ser19Cys and Gly397Arg) were found in two subjects with unknown pathogenicity. No GCH1 and TH mutation was found in 40 unrelated normal Han Chinese controls. GCH1 mutation is the main etiology of familial DRD. Three novel GCH1 mutations were identified in this study. Genetic heterogeneity and incomplete penetrance were quite common in DRD patients, especially in sporadic cases. Genetic screening may help establish the diagnosis of DRD; however, a negative GCH1 and TH mutation test would not exclude the diagnosis.